The additive effect of genetic and metabolic factors in the pathogenesis of nonalcoholic fatty liver disease - Yuya Seko; Kanji Yamaguchi; Kota Yano; Yusuke Takahashi; Kento Takeuchi; Seita Kataoka; Michihisa Moriguchi; Yoshito Itoh (Scientific Reports, 2022)
Abstract Both genetic and metabolic factors influence the pathology of nonalcoholic fatty liver disease (NAFLD). The aim of this retrospective study was to evaluate the impact of these factors at each stage of disease. We analysed the impact of obesity, diabetes mellitus and genetic risk factors (alleles of PNPLA3 or HSD17B13) on nonalcoholic steatohepatitis (NASH), significant fibrosis (stage ≥ 2) and advanced fibrosis (stage ≥ 3) in 346 patients. Genetic high risk was defined as having at least 2 risk alleles. The median age was 59 years, median body mass index was 27.1 kg/m2, and 46.8% had diabetes mellitus. Obesity was a risk factor for NASH, significant fibrosis, and advanced fibrosis. Diabetes mellitus increased the risk of NASH. Genetic risk increased the risk of significant and advanced fibrosis. Odds ratios for NASH, significant fibrosis and advanced fibrosis increased with the number of genetic and metabolic risk factors. The patients with both metabolic and genetic risks had an odds ratio of 12.30 for NASH, 5.50 for significant fibrosis, and 6.25 for advanced fibrosis. Factors strongly impact on the pathology of NAFLD differed according to the fibrosis stages. Synergistic effects were observed between genetic and metabolic factors at all stages.